Shielding effect of monovalent and divalent cations on solid-phase DNA hybridization: surface plasmon resonance biosensor study - Springer, Tomás; Sípová, Hana; Vaisocherová, Hana; Stepánek, Josef; Homola, Jirí (Nucleic acids research, 2010)
Solid-phase hybridization, i.e. the process of recognition between DNA probes immobilized on a solid surface and complementary targets in a solution is a central process in DNA microarray and biosensor technologies. In this work, we investigate the simultaneous effect of monovalent and divalent cations on the hybridization of fully complementary or partly mismatched DNA targets to DNA probes immobilized on the surface of a surface plasmon resonance sensor. Our results demonstrate that the hybridization process is substantially influenced by the cation shielding effect and that this effect differs substantially for solid-phase hybridization, due to the high surface density of negatively charged probes, and hybridization in a solution. In our study divalent magnesium is found to be much more efficient in duplex stabilization than monovalent sodium (15 mM Mg2+ in buffer led to significantly higher hybridization than even 1 M Na+). This trend is opposite to that established for oligonucleotides in a solution. It is also shown that solid-phase duplex destabilization substantially increases with the length of the involved oligonucleotides. Moreover, it is demonstrated that the use of a buffer with the appropriate cation composition can improve the discrimination of complementary and point mismatched DNA targets.
Keywords: kationty dvojmocné; kationty jednomocné; Spectrophotometry, Ultraviolet; spektrofotometrie ultrafialová; Nucleic Acid Hybridization; Sodium; hybridizace nukleových kyselin; Cations, Divalent; Surface Plasmon Resonance; Cations, Monovalent; hořčík; povrchová plasmonová rezonance; Magnesium; DNA Probes; chybné párování bází; Base Pair Mismatch; sodík; DNA sondy